PP10 Anatomy Associated with The Production of Specialized Metabolites in Piper Peltatum and Its Application in Phytopathogen Control - Pizarro Ramirez, Juan Felipe; MARQUINEZ-CASAS, Xavier; RODRIGUEZ-SANCHEZ, Laura; CELIS-FIGUEROA, Maryurith; MARTIN-ALFONSO, Astrid; MATULEVICH-PELAEZ, Javier Andrés; PATIÑO-LADINO, Oscar Javier; PRIETO-RODRÍGUEZ, Juliet (Revista Productos Naturales, 2025)
Piper peltatum is a species belonging to the Piper genus of the Piperaceae family. Species within this genus have been studied for their ethnobotanical relevance, associated with the accumulation of specialized metabolites in certain tissues with antifungal, antibacterial, and antioxidant properties